Standardizing UX Dashboards: A Framework Integrating Usability Metrics, Benchmarks, and Glossaries for Managerial Insight - Prasetyo, Muhammad Teguh; Rokhman, Bagus Insanu (Data : Journal of Information Systems and Management, 2024)
User experience (UX) dashboards serve as essential tools for translating complex digital interaction data into strategic business insights. This study aims to construct a comprehensive dashboard framework by integrating international usability standards, validated public benchmarks, and a structured glossary of UX metrics. Drawing upon ISO 9241 11, ISO/IEC 25010, the HEART framework, and benchmark data from sources like CrUX, Mixpanel, and Baymard Institute, the proposed model categorizes UX metrics into subjective (e.g., SUS, UMUX Lite), behavioral (e.g., DAU/MAU), and technical (e.g., LCP, INP, CLS) dimensions. The study applies a structured classification of metrics grounded in usability standards and validated benchmarks. Key findings highlight benchmark and glossary tables that consolidate formulas, interpretation guidelines, and sector averages. For instance, SUS scores above 68 and UMUX Lite above 70 indicate acceptable usability, while Core Web Vitals thresholds remain critical. The framework offers practical guidance for consistent and real-time UX evaluations and supports future empirical validation.